The impossibility of Palestine history, geography, and the road ahead - Kamrava, Mehran (Yale University Press, 2016)
The "two-state solution" is the official policy of Israel, the United States, the United Nations, and the Palestinian Authority alike. However, international relations scholar Mehran Kamrava argues that Israel's "state-building" process has never risen above the level of municipal governance, and its goal has never been Palestinian independence. He explains that a coherent Palestinian state has already been rendered an impossibility, and to move forward, Palestine must redefine its present predicament and future aspirations.